EigenGait: Motion-Based Recognition of People Using Image Self-Similarity - BenAbdelkader, Chiraz; Cutler, Ross; Nanda, Harsh; S. Davis, Larry (Lecture Notes in Computer Science, 2001)
We present a novel technique for motion-based recognition of individual gaits in monocular sequences. Recent work has suggested that the image self-similarity plot of a moving person/object is a projection of its planar dynamics. Hence we expect that these plots encode much information about gait motion patterns, and that they can serve as good discriminants between gaits of different people. We propose a method for gait recognition that uses similarity plots the same way that face images are used in eigenface-based face recognition techniques. Specifically, we first apply Principal Component Analysis (PCA) to a set of training similarity plots, mapping them to a lower dimensional space that contains less unwanted variation and offers better separability of the data. Recognition of a new gait is then done via standard pattern classification of its corresponding similarity plot within this simpler space. We use the k-nearest neighbor rule and the Euclidian distance. We test this method on a data set of 40 sequences of six different walking subjects, at 30 FPS each.We use the leave-one-out cross-validation technique to obtain an unbiased estimate of the recognition rate of 93%.